Entrepreneurial Competencies as an Entrepreneurial Distinctive: An Examination of the Competency Approach in Defining Entrepreneurs - LI, Xiang (Institutional Knowledge at Singapore Management University, 2009)
Entrepreneurship is of critical importance to the modern economy. Researchers have studied entrepreneurship for decades. In recent years, significant relationship between entrepreneurial competencies and firm performance has been reported in empirical studies. Applying the competency approach, researchers have assumed that entrepreneurial competency differentiates entrepreneurs from non-entrepreneurs without empirically examining if this is the case. The research conducted under this thesis addresses this gap. Drawing upon a thorough literature review regarding the components, antecedents and performance outcomes of the entrepreneurial competency, we propose the following hypothesis: the entrepreneurs generally possess higher level of entrepreneurial competencies than the non-entrepreneurs, and the entrepreneurs and the non-entrepreneurs can be discriminated based on their entrepreneurial competency level. A survey is conducted among the business owners and the managers. Employing discriminant analysis, we find empirical evidence that the business owners generally possess higher level of entrepreneurial competencies than the managers, and the business owners and the managers can be discriminated based on their entrepreneurial competency level, which supports our hypothesis.